KETERKAITAN PENGEMBANGAN KARIR DAN STRES EKRJA PERAWAT DI RSU AISYIYAH SITI FATIMAH TULANGAN - Ema Retiyaningsih; Ike Prafita Sari; Yudha Laga Hadi Kusuma (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2025)
Nurses work by providing 24 hour care to patients which causes nurses to be faced with the emotional burden of various stressors. One of the causes of dissatisfaction at work is related to career satisfaction obtained. The aim of the research is to determine the relationship between career development and workstress in nurses. This research design is correlational with a cross-sectional approach. The independent variable is career development and the dependent variable is work stress. The population of this study were all nurses in the inpatient room at Aisyiyah Siti Fatimah Tulangan Sidoarjo Hospital, totaling 65 nurses. The sample was taken using a simple random sampling technique of 56 respondents. Data was collected using a questionnaire instrument and tested using the Spearman Rho test. The research results showed that half of the respondents who stated that their career development was negative experienced work stress in the moderate category, namely 7 respondents (50%). Most of the respondents who stated that career development in hospitals was positive experienced work stress in the mild category, 31 respondents (73.8%). The Spearman rho test results obtained values of ρ = 0.000, α = 0.05, r = 0.573. This shows that the value of ρ = 0.000 < α = 0.05 so that H0 is rejected and H1 is accepted, so there is a relationship between career development and work stress for nurses at RSU 'Aisyiyah Siti Fatimah Tulangan Sidoarjo. Based on the correlation coefficient value, the value r = 0.573 is obtained, this shows that the close relationship between the two variables is quite strong. Nurses should be able to make good use of rest time so that they do not experience fatigue and need to create harmonious cooperation so that working conditions are good and enjoyable so that work stress is reduced.